The Lecithin and anionic lipids as an imitation of the lipid membrane in Parallel Artificial Membrane Permeation Assay (PAMPA) blood –brain barrier Models - Otasevic, Svetlana; Vojinovic, Tanja (Progress in Nutrition, 2020)
Background/Aim: One of the biggest challenges today is producing pharmaceutical forms of drugs for a successful treatment of pathological disorders of the central nervous system (CNS), bearing in mind that the brain tissue is highly selective when it comes to permeation of all substances, particularly drugs. In vitro Parallel Artificial Membrane Permeation Assay (PAMPA) drug permeability assay is an extremely important experimental model in the process of drug development. The aim of this study is to modify this model in order to test drug permeability through the blood-brain barrier. Methods: The substances with pharmacological activity tested in this study are the following: theophylline, sulfasalzine, risperidone, haloperidol, lidocaine and propranolol. We studied some of the key parameters which are important for good prediction of permeability – lipid composition and buffer composition. We also investigated the effect of co-solvents in the donor compartment and surfactants in the acceptor compartment, as well as the influence of the anionic lipid composition on drug permeability through the blood-brain barrier. As co-solvents, we used polyethylene glycol 200 (PEG 200) at concentrations of 1% and 0.24%, and as surfacants we applied sodim lauryl sulfate (SLS) at concentrations of 2% and 0.5%. In addition, the influence of lecithin and the anionic lipid composition was investigated and the following lipids were used for this purpose: 1,2-dioleoyl-sn-glycero-3-[phospho-L-serine] (PS18: 1), 1,2-dioleoyl-sn-glycero-3-phosphocholine (PC18: 1), and cholesterol. Results: The use of PEG 200 at concentrations of 1% and 0.24% proved to be good and allowed for a proper classification of the substances into those of high and low permeability. SLS at concentrations of 2 and 0.5% impaired the integrity of the lipid membrane, with the solution penetrating from the acceptor into the donor compartment. A brief experiment with methanol and SLS combined, showed that the membrane integrity remains preserved. The anionic lipid composition also proved favourable and the substances tested were properly classified into those of high and low permeability. Conclusion: The lipids that were used as an imitation of lipid membrane such as a 10% lecithin and combination of 1,2-dioleoyl-sn-glycero-3-[phospho-L-serine] (PS18: 1), 1,2-dioleoyl-sn-glycero-3-phosphocholine (PC18: 1) and cholesterol in the anionic-pampa model proved to be good and allowed for a proper classification of the substances into those of high and low permeability.